Monitoring of landfill influences on groundwater - Brenčič, Mihael (Geologija, 2004)
Landfills of waste present serious threat to groundwater. To prevent groundwater pollution from landfill monitoring is performed. Rule of groundwater pollution monitoring from dangerous substances implements principles in Slovene legislation. In everyday practice certain questions arose since validity of the rule. These questions are about responsible parties in monitoring, groundwater distribution in space, target groundwater units, characterization level of the landfill and its surroundings, background values in groundwater, table of content of groundwater monitoring plan, quality of groundwater monitoring network, phases of monitoring, maintenance of monitoring network and activation of piezometers.